Optimization of TCSC Placement and Capacity to Improve Transient Stability of Transmission Systems - Srimadewi, Putri (Cattleya Darmaya Fortuna, 2024)
This study proposes an integrated optimization framework for the location and capacity determination of Thyristor Controlled Series Capacitor (TCSC) to improve the transient stability of a high-penetration renewable energy transmission system. The system dynamics model is evaluated in the electromagnetic-transient domain for various representative disturbances, while load and power injection uncertainties are modeled using Latin Hypercube Sampling. The objective function is formulated in a multi-objective manner to balance stability margin enhancement, rotor oscillation damping, ROCOF reduction, voltage recovery, and investment cost efficiency. The NSGA-II algorithm is used to obtain the Pareto set under the operational constraints of voltage, power flow, and reactance modulation limits of the TCSC. In a case study of a modified 150 kV network, the Pareto solution shows an increase in Critical Clearing Time in the order of tens of milliseconds, a decrease in peak ROCOF, an increase in minimum post-fault voltage, and a reduction in network losses compared to the condition without TCSC. Sensitivity analysis shows that the performance remains robust to variations in load and plant input power, thus the proposed framework provides practical guidelines for transmission operators to select the most effective TCSC configuration within budget constraints and reliability targets.